Lobar Approach to Breast Ultrasound (Springer International Publishing, 2018)
This book focuses on the lobar anatomy of the breast and on the sick lobe concept - a novel theory of breast cancer development that is gaining ever wider acceptance - and explores their significance for innovative surgical treatment. Special attention is paid to the role of ductal echography, a technique capable of clearly depicting the structures of cancer in relation to the structures of the sick lobe. Having established a sound theoretical and practical basis through detailed coverage and correlation of anatomy, pathology, and imaging appearances, the book goes on to describe a revolutionary surgical approach particularly suitable for the treatment of multifocal and multicentric breast carcinomas. Such tumors account for more than a third of all cases of breast carcinoma and are often treated by mastectomy. The proposed new breast-conserving technique yields excellent cosmetic results and entails a very low risk of recurrence. The book will appeal to a wide readership, including radiologists, surgeons, oncologists, pathologists, as well as residents.